2020
DOI: 10.1002/jat.3987
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic (90‐day) toxicity assessment of Somacy‐FP100, a lipopolysaccharide‐containing fermented wheat flour extract from Pantoea agglomerans

Abstract: Pantoea agglomerans is a Gram‐negative bacterium that is ubiquitous in the environment, colonizing animals, humans, and numerous plants, including cotton and wheat. A lipopolysaccharide‐containing fermented wheat flour extract from P. agglomerans (Somacy‐FP100) is proposed for use as a food ingredient for individuals seeking foods for healthy aging. Previously published genotoxicity studies with Somacy‐FP100 reported its lack of genotoxicity in vitro, but a subchronic toxicity study has not yet been performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…On the other hand, Pseudomonas gessardii has been indicated as a potential biocatalyst for the synthesis of bromohydrins [ 106 ] and for enzyme therapy [ 107 ]. Additionally, P. agglomerans is a promising multifunctional microorganism in biorefineries, namely in converting the hemicellulose fraction of plant biomass into valued-added products [ 108 ] and in producing plant-based food ingredients [ 109 ]. It is also a source of antibiotics against multidrug-resistant bacteria [ 110 ] and able to degrade waste [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Pseudomonas gessardii has been indicated as a potential biocatalyst for the synthesis of bromohydrins [ 106 ] and for enzyme therapy [ 107 ]. Additionally, P. agglomerans is a promising multifunctional microorganism in biorefineries, namely in converting the hemicellulose fraction of plant biomass into valued-added products [ 108 ] and in producing plant-based food ingredients [ 109 ]. It is also a source of antibiotics against multidrug-resistant bacteria [ 110 ] and able to degrade waste [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, we humans have already unconsciously orally ingested LPS derived from food. In fact, animal safety studies have confirmed that LPS is not toxic when administered orally, even at doses of 500-4500 mg/kg, which are far higher than doses that are toxic when administered intravenously (16)(17)(18). Therefore, it is thought that the pharmacokinetics of LPS are completely different between intravenous and oral administration, resulting in different pharmacological effects.…”
Section: Distinct Mechanism Between Oral and Intravenous Administrati...mentioning
confidence: 99%
“…In fact, the bacteria are also used as a food preservative ( 39 , 40 ). In addition, the safety of oral administration of P. agglomerans -derived LPS is guaranteed by objective tests based on Organization for Economic Co-operation and Development (OECD) standards ( 17 ). Therefore, we focused on this P. agglomerans -derived LPS as a food-experienced LPS, and elucidated the preventive and therapeutic effects of OAL in various disease models.…”
Section: Introductionmentioning
confidence: 99%
“…However, environment- or food-derived LPS does not seem to induce inflammatory responses [ 8 , 12 ]. In addition, no toxicity or exacerbated inflammatory responses after oral and transdermal LPS administration have been observed in animal models [ 12 , 13 ]. This means that the response varies depending on the LPS dose and route of administration.…”
Section: Introductionmentioning
confidence: 99%